List of non‐EU phytoplasmas of Cydonia Mill., Fragaria L., Malus Mill., Prunus L., Pyrus L., Ribes L., Rubus L. and Vitis L. (13th January 2020) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; Potting, Roel; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health prepared a list of non‐EU phytoplasmas of Cydonia Mill., Fragaria L., Malus Mill., Prunus L., Pyrus L., Ribes L., Rubus L. and Vitis L. A systematic literature review and search of databases identified 27 phytoplasmas infecting one or more of the host genera under consideration. These phytoplasmas were assigned to three categories. The first group (a) consists of 10 non‐EU phytoplasmas, known to occur only outside the EU (' Candidatus Phytoplasma australiense', ' Ca . P. hispanicum', ' Ca . P. pruni'‐related strain (NAGYIII), ' Ca . P. pyri'‐related strain (PYLR) and Buckland valley grapevine yellows phytoplasma) or having only limited presence in the EU (' Ca . P. aurantifolia'‐related strains, ' Ca . P. fraxini', ' Ca . P. phoenicium', ' Ca . P. trifolii' and ' Ca . P. ziziphi'). The second group (b) consists of three non‐EU phytoplasmas, whose presence in the target plant species is not fully supported by the available literature. The third group (c) consists of 14 phytoplasmas with substantial presence in the EU (i.e. they are originally described or reported from the EU or known to occur or be widespread in some EU Member States or frequently reported in the EU). Phytoplasmas of categories (b) and (c) were excluded at this stage from further categorisation efforts. One phytoplasma from category (a) (' Ca . P. phoenicium') was excluded from further categorisation, as a pest risk assessment has been performed by EPPO. Comments provided by the EU Member States were integrated in the opinion. The main uncertainties of this listing concern: the geographic distribution and prevalence, the taxonomy, biology and host range. The phytoplasmas considered as non‐EU and whose presence in target plant species is fully supported by literature (category (a)) are categorised by the Panel in a separate opinion.